A Global Survey of Outlaw Motorcycle Gang Formation. Issue 12 (1st December 2020) - Lauchs, Mark
ABSTRACT: Outlaw Motorcycle Gangs are receiving increased attention by academics around the world. However, the field is in need of global data on how, when, where and why clubs form before any generalised conclusions can be drawn. This paper begins this process by attempting to identify every club that has formed in the world by location and date. 18 months of searching online through websites and social media identified 5072 separate clubs, which were then grouped by region and date. This data shows different trends of club formation in different regions. The data shows Western Nations formed clubs much earlier than other regions, but that Scandinavia, South America and East Asia are continuing to form new clubs at an increasing rate. Despite the USA being the country of origin of the culture, it only has 18% of all clubs. This paper concludes with suggestions for future research questions illuminated by the data, that try to explain the popularity of the culture and the environmental circumstances that lead to club formation.